Assessment of the correlation between TMPA satellite-based and rain gauge rainfall - Syaza Nadia , Mohdin (2015)
Accurate rainfall data at high spatial and temporal resolution is necessary for many hydrological and water management application, and especially in data scarce river watershed. Satellite-based rainfall estimation can be used as an alternative source of rainfall information, but need area-specific calibration and validation. The main study focused was to assess the correlation between TMPA satellite-based rainfall and raingauge rainfall for Peninsular Malaysia, for a period of five years (July 2009 - June 2014). The specific objectives include; (i) to establish the satellite-based rainfall of study area, and (ii) to analyse the correlation between satellite-based rainfall and raingauge rainfall. In this study, Tropical Rainfall Measuring Mission Multi-satellite Precipitation Analysis (TMPA) version 7 satellite-based rainfall data obtained from public domain, and monthly rainfall from Jabatan Pengairan dan Saliran, Malaysia (JPS) rain-gauge stations were used. Meanwhile, Geographical Information System (GIS) technique was used to established monthly rainfall maps for study area. Both type of monthly rainfall are retrieved at correspond location. The correlation between satellite-based rainfall and rain-gauge rainfall is statistically analysed. The monthly rainfall values estimated from satellite-based and the measured values shows a very good agreement (correlation coefficients of 63%). The regression line fitted through the origin has a slope of 0.83. For calibrated purposed, regression analysis was carried out. Result indicated good correlation between monthly rainfall TMIPA with the corresponding rain-gauge records (r 2 = 0.55: p<O.00l, n=1116). The validity of these techniques was tested using Nash—Sutcliffe efficiency (0.80). Meanwhile, the correlation of the monthly satellite-based calibrated rainfall and the measured rainfall increase (r=94%: slope=0.94).